2021
DOI: 10.1177/13670069211019466
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation and attitudes toward code-switching: A bidimensional framework

Abstract: Aims and objectives: Code-switching, the spontaneous switching from one language to another within a single speech event, is often performed by bilinguals who have mastered a communicative competence in two languages. It is also a social strategy – using linguistic cues as a means to index social categories and group solidarity. Code-switching is, therefore, linked to attitudes, seen as a reflection of the speaker and their values and identities. Traditionally perceived negatively, attitudes toward code-switch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 56 publications
(63 reference statements)
0
5
1
Order By: Relevance
“…This finding also builds on existing evidence of social identity theory ( Tajfel & Turner, 1986 ), where higher identification with an in-group leads to higher attribution of solidarity toward the language spoken by that in-group. While recent work demonstrated that the in-group or reference group may relate to broader elements of linguistic identity or community-level subgroups (e.g., frequent code-switchers, other bilingual biculturals) in Cantonese-English bilinguals ( Yim & Clément, 2019 , 2021 ), our findings suggest that the in-group with which participants identified can also relate to others who share their first language. In addition, we did not find any evidence of internalized in-group stigma ( Hughes et al, 2015 ), such that the relative minority status of English within the French-dominant province of Québec could be offset by the role of English as a global lingua franca , and vice versa.…”
Section: Discussioncontrasting
confidence: 78%
“…This finding also builds on existing evidence of social identity theory ( Tajfel & Turner, 1986 ), where higher identification with an in-group leads to higher attribution of solidarity toward the language spoken by that in-group. While recent work demonstrated that the in-group or reference group may relate to broader elements of linguistic identity or community-level subgroups (e.g., frequent code-switchers, other bilingual biculturals) in Cantonese-English bilinguals ( Yim & Clément, 2019 , 2021 ), our findings suggest that the in-group with which participants identified can also relate to others who share their first language. In addition, we did not find any evidence of internalized in-group stigma ( Hughes et al, 2015 ), such that the relative minority status of English within the French-dominant province of Québec could be offset by the role of English as a global lingua franca , and vice versa.…”
Section: Discussioncontrasting
confidence: 78%
“…Teachers can improve their students' language learning experiences, deepen their comprehension of linguistic structures, and increase their level of language proficiency and identity by carefully using code-switching for metalinguistic reasons. (Yim & Clément, (2021).…”
Section:  Results and Discussionmentioning
confidence: 99%
“…Having a communicative proficiency in two languages is a social strategy that also provides integration between two cultures. In a study investigating the attitudes of spontaneous switching from one language to another during a single conversation with cultural identity, it was found that this transition is associated with bicultural identity (Yim and Cle ´ment, 2021). There are studies showing that cultural identity is shaped by a sense of privilege and belonging that is never fully abandoned.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%